A Casa Impossível: a ação performativa e a idiorritmia na construção de relações com a cidade - Oliveira Filho, João Vilnei de (2016)
It was over the house itself, “over- through-and-with it”, that the “Impossible House” was built. During the development of my research, the feelings that usually emanate from its traditional concept - such as security, intimacy, common and shared life – gave ground for a very particular method of appropriation of the city, experienced here as an artistic production space. A city that needs to morph into a house to be worked on. The “Impossible House” is a theoretical and practical research, centred on the development of several initiatives, within the city grounds, to promote the emergency of intimate relationships. From the discussion of texts addressing performance, house, game, city and community arose a group of artists and authors in pursuit of the deconstruction – on different levels and in different ways – of the boundaries between public and private spaces, inside and out, street and room, house and city. By the application of methods and concepts pertaining the discussed themes, this research demonstrates the relationship between the personal, social and academic universes. This characteristic present at the final document’s organization which, in it’s first section, reflects on the research construction stages, highlighting each of the fore fronted concepts. Firstly, the idiorythmie, stated by Roland Barthes as a social experience of shared life and the configuration of space by the contemporary artistic production. Secondly, the possibility of creation of a research method, in art, grounded on “Crítica do Processo” – discussed by Cristina Salles – and “cartography”, imbibing from the “game” theory presented by Huizinga and Caillois, where chance and routine are perceived as building tools and “performance” is taken as an artistical practice which is, quintessentially, playable; Thirdly, the transition between the idea of prototype into the one of action, having the house as a space of intimacy deepening.This document was built with the intention of allowing the reader to define his own reading path, trying to bring his experience closer to the one which was lived during the construction of the research itself.The particularities and reasoning to this uncommon reading format are presented at Chapter 2, whereupon the reader is prepared for the next chapter, where the 26 actions developed in the scope of this research are unfolded, in detail, as well as all the defining materials for the investigation design. The final analysis shows the difficulties involved in a project as Impossible House”, discusses the text construction as a practical action and highlights importance for the artist that uses the city as an intervention space to intimately relate to it.